The geopolymerization hydration kinetics governing the solidification of coal and wood biomass ash cementless Concrete. - Cheah, Chee Ban (Universiti Sains Malaysia, 2016)
The activation of the Class F coal fly ash using the rubber wood ash is anticipated to produce a stable geopolymer binder matrix which is dimensionally and mechanically stable for used a primary binder of concrete.The reaction mechanism of the hydrated rubber wood ash-coal fly ash paste was examined using FTIR, TGA and SEM-EDX assessment.